Traffic forecasting on national roads - Jerzy Kukiełka (Budownictwo i Architektura, 2012)
The purpose of this paper is the analysis of traffic load on road pavement and it forecasting, in aspect of designing the reconstruction of roads and pavement strengthening. At present modeling method is a method that offers highest level of traffic load forecasting. Preparation of the digital model of road network and traffic load, which take place on it, allows to eliminate many drawbacks of existing methods of forecasting. For accurate predictions of heavy vehicles by model it is necessary to build the best possible knowledge base of traffic load which is present on the existing road network in particularly based on the largest number of measure spots to both classification and pre-selection of weight classes such as WIM-P.